Contro la pandemia. Analisi etico-giuridica del Piano pandemico 2021-2023 (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In this paper, after a general description of the Pandemic Plan 2021-2023, the bioethical criteria that are the basis of the current document will be critically discussed. Attention will also be paid to the issue of allocative justice and the proposed meaning and role attributed to the fundamental right to health will be considered. The problems that emerge from the redefinition of the right to health in the document will be highlighted. Finally, thinking about future pandemic scenarios, for a greater effectiveness of the Plan, some ethical - legal issues will be examined that should be better considered.
Keywords: Pandemic; allocative justice; fundamental right to health; ethics; law